Molecular Research in Rice Agronomically Important Traits - Hori, Kiyosumi; Shenton, Matthew (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume presents recent research achievements concerning the molecular genetic basis of agronomic traits in rice. Rice (Oryza sativa L.) is the most important food crop in the world, being a staple food for more than half of the world's population. Recent improvements in living standards have increased the worldwide demand for high-yielding and high-quality rice cultivars. To achieve improved agricultural performance in rice, while overcoming the challenges presented by climate change, it is essential to understand the molecular basis of agronomically important traits. Recently developed techniques in molecular biology, especially in genomics and other related omics fields, can reveal the complex molecular mechanisms involved in the control of agronomic traits. As rice was the first crop genome to be sequenced, in 2004, molecular research tools for rice are well-established, and further molecular studies will enable the development of novel rice cultivars with superior agronomic performance.